Journalism in transition in front of the V ipcc report, The paris agreement and The sustainable development goals - Fernández Reyes, Rogelio; Águila Coghlan, Juan Carlos (Ámbitos. Revista Internacional de Comunicación, 2017)
The Intergovernmental Panel on Climate Change (IPCC) recognizes that climate change is clear, unequivocal, has already generated impacts on all continents and oceans, and mitigation and adaptation will be necessary to avoid harmful climatic impacts (IPCC 2014). The Sustainable Development Goals have climate change as one of the main challenges. The Paris Agreement (2015) has set itself the goal of “keeping the average global temperature rise well below 2° C above pre-industrial levels and continuing efforts to limit that temperature rise to 1,5° C”. The IPCC indicates that there is little time left to prevent the average temperature rises above 2° C from pre-industrial levels. In this essay, it is considered that in order to achieve -or approach- the objective of increasing the temperature not to exceed 1.5 ° C, a transformational change, that is, systemic, must take place over a short period of time. It is proposed to reflect on how to seek journalism in transition that, without renouncing rigor and objectivity, places sustainability as a reference axis. And we reflect on what elements may be interesting in communicative practices before the V IPCC Report, the Sustainable Development Goals and the Paris Agreement.